Types of combined neurovascular injuries of the extremities - I. V. Pertsov (Zaporozhye State Medical University, 2014)
Combined injuries of neurovascular structures are associated with poor results of limb function restoration, often lead to disability and lower quality of life. Aim. To determine the features of regional blood flow of the extremities in patients with combined neurovascular structures injury. Methods and results. In 98 patients indicators of limb microcirculation and tissue perfusion were established using laser Doppler. In nerve autonomous zone an increase of neurogenic tone (NT) ≥50% and a significant decrease in microcirculation (PM) ≤ 60% were registered as compared with contralateral limb. Conclusion. 3 types of damage are pointed out, knowledge of which selects the pathogenetic types of interventions and influences treatment strategy and results of restoration of limb function significantly.